The V-ATPase regulates localization of the TRP Ca2+ channel Yvc1 in response to oxidative stress in Candida albicans - Liping Peng; Qilin Yu; Hangqi Zhu; Nali Zhu; Bing Zhang; Henan Wei; Jiachun Xu; Mingchun Li (Elsevier, 2020)
The vacuolar-type H+-ATPase (V-ATPase) is a highly conserved protein complex among the eukaryotic cells. We previously revealed that both the V-ATPase and the transient receptor potential (TRP) channel Yvc1 are involved in oxidative stress response (OSR). However, the relationship between V-ATPase and Yvc1 during OSR remains unknown. In this study, disruption of the V-ATPase-encoding genes VPH2 and TFP1, similar with disruption of YVC1, caused H2O2 hypersensitivity and enhancement of vacuolar membrane permeability (VMP) under oxidative stress. Further investigations showed that unlike the wild type strain with vacuole membrane-localized Yvc1, both vph2Δ/Δ and tfp1Δ/Δ had Yvc1 localization in the vacuole cavity, indicating that disruption of VPH2 or TFP1 impaired normal vacuolar membrane-localization of Yvc1. Interestingly, addition of CaCl2 alleviated the growth defect of vph2Δ/Δ and tfp1Δ/Δ under oxidative stress, leading to prevention of VMP, decrease in ROS levels and activation of OSR. In contrast, addition of the Ca2+ chelating agent glycol-bis-(2-aminoethylether)-N,N,N',N'-tetraacetic acid (EGTA) aggravated H2O2 hypersensitivity of the mutants. These results showed that the V-ATPase plays an important role in maintenance of normal Yvc1 localization, which contributes to Ca2+ transport from the vacuoles to the cytosol for activation of OSR. This work sheds a novel light on the interaction between V-ATPase and Ca2+ transport for regulation of OSR in C. albicans.